Connective tissue disease is associated with the risk of posterior reversible encephalopathy syndrome following lung transplantation in Korea - Tae Jung Kim; Hyun Joo Lee; Samina Park; Sang-Bae Ko; Soo-Hyun Park; Seung Hwan Yoon; Kwon Joong Na; In Kyu Park; Chang Hyun Kang; Young Tae Kim; Sun Mi Choi; Jimyung Park; et al. (Acute and Critical Care)
Background Posterior reversible encephalopathy syndrome (PRES) is a rare complication of lung transplantation with poorly understood risk factors and clinical characteristics. This study aimed to examine the occurrence, risk factors, and clinical data of patients who developed PRES following lung transplantation. Methods A retrospective analysis was conducted on 147 patients who underwent lung transplantation between February 2013 and December 2023. The patients were diagnosed with PRES based on the clinical symptoms and radiological findings. We compared the baseline characteristics and clinical information, including primary lung diseases and immunosuppressive therapy related to lung transplantation operations, between the PRES and non-PRES groups. Results PRES manifested in 7.5% (n=11) of the patients who underwent lung transplantation, with a median onset of 15 days after operation. Seizures were identified as the predominant clinical manifestation (81.8%, n=9) in the group diagnosed with PRES. All patients diagnosed with PRES recovered fully. Patients with PRES were significantly associated with connective tissue disease-associated interstitial lung disease (45.5% vs. 18.4%, P=0.019, odds ratio=9.808; 95% CI, 1.064–90.38; P=0.044). Nonetheless, no significant variance was observed in the type of immunotherapy, such as the use of calcineurin inhibitors, blood pressure, or acute renal failure subsequent to lung transplantation. Conclusions PRES typically manifests shortly after lung transplantation, with seizures being the predominant initial symptom. The presence of preexisting connective tissue disease as the primary lung disease represents a significant risk factor for PRES following lung transplantation.